Trazabilidad de productos y subproductos forestales maderables en función a la aplicación del libro de operaciones en los centros de transformación primaria, acopio, depósitos y centros de comercialización, Loreto – 2022 - Vasquez Rengifo, Florinda Jhoana del Jesus (2023)
The present study was carried out in the primary transformation centers, collection, warehouses and marketing centers of the metropolitan city of Iquitos, with the purpose of knowing the traceability of timber forestry products and sub - products in the primary transformation centers, collection, warehouses and marketing centers base don the Book of Operations. From the obtained results, traceability in Loreto region is in an advanced state, reaching 61% approval. The operations book has only been implemented in the primary production centers (sawmills), leaving the marketing centers for a second stage. People dedicated to forestry activity have full knowledge of the Forestry and Wildlife Law as well as the existence of article 171 that establishes the operations book and are aware of its importance. There is awareness that traceability must be applied not only to forest products but also to all those that generate environmental pollution. There is Little knowledge of the regulations of the Forestry and Wildlife Law because it is very bulky and generates greater bureaucracy.